2014
DOI: 10.1128/iai.01419-13
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Matrix Exoproteins Induce a Protective Immune Response against Staphylococcus aureus Biofilm Infection

Abstract: The Staphylococcus aureus biofilm mode of growth is associated with several chronic infections that are very difficult to treat due to the recalcitrant nature of biofilms to clearance by antimicrobials. Accordingly, there is an increasing interest in preventing the formation of S. aureus biofilms and developing efficient antibiofilm vaccines. Given the fact that during a biofilm-associated infection, the first primary interface between the host and the bacteria is the self-produced extracellular matrix, in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 78 publications
2
53
0
2
Order By: Relevance
“…aureus is frequently associated with formation of biofilm in the mammary gland, making antibiotic therapy of bovine mastitis difficult (Melchior et al 2006). Microorganisms residing in biofilm respond poorly to antimicrobial agents and resist host innate immune mechanisms (Thurlow et al 2011;Zecconi & Scali 2013;Gil et al 2014). Upon entry into the mammary gland, S. aureus attaches to the epithelial lining of the mammary gland using specific receptors and begins the process of colonization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus is frequently associated with formation of biofilm in the mammary gland, making antibiotic therapy of bovine mastitis difficult (Melchior et al 2006). Microorganisms residing in biofilm respond poorly to antimicrobial agents and resist host innate immune mechanisms (Thurlow et al 2011;Zecconi & Scali 2013;Gil et al 2014). Upon entry into the mammary gland, S. aureus attaches to the epithelial lining of the mammary gland using specific receptors and begins the process of colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Maira-Litran et al 2005;Prenafeta et al 2010;Skurnik et al 2010;Gil et al 2014). Use of the slime-associated antigenic complex (SAAC) of S. aureus has been reported to protect against localized and systemic infections of S. aureus in mice(Cywes-Bentley et al 2013) but failed to protect against intramammary infections in cows, only leading to a reduction in the multiplication of S. aureus in the mammary gland(Prenafeta et al 2010) Maira-Litran et al (2005).…”
mentioning
confidence: 98%
“…With respect to matrix composition, S. aureus biofilms consist mainly of polysaccharides (poly-N-acetylglucosamine and teichoic acid), extracellular matrix proteins, and DNA released from bacteria (30)(31)(32)(33), but the relative amounts of these components may differ among the biofilms formed from different strains due to differences in the expression of the genes regulating biofilm formation (32,34). The matrix composition of the biofilms formed by the strains used in our study is not known, but we observed major differences in the capacities of the strains to form biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, two different antigens were used: SERP0630 (MenD) (for S. epidermidis) and SACOL1138, or iron-regulated surface determinant B (IsdB) (for S. aureus). With S. aureus, a recent study reported that extracellular proteins found in the biofilm matrix could induce a protective immune response that prevented subsequent infections (322).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%